Udział kobiet w mediach a problematyka stereotypów płci - BALCZYŃSKA-KOSMAN, Alina (Przegląd Politologiczny, 2018)
The role women play in the media can be analyzed in terms of their activity – women as creators of messages, or passivity – women as the recipients of mass messages. The latter aspect causes most controversy and frequently leads to the creation of sexual stereotypes. The range of male and female images in the mass media is highly diversified and not necessarily objective. While women tend to be increasingly present in the media, and the number of programs they prepare increases, men continue to prevail in the media sector. They hold a definite majority of managerial posts and more frequently act as experts and commentators on social and political events. The Communication of the European Commission for 2006–2010 stresses the role of the media and information campaigns in the elimination of sexual stereo- types. In 2010, the Commission adopted a new five-year strategy to facilitate better use of female potential. It should be the superior objective of a policy of gender equality in the media to broadcast balanced messages free from stereotypes. It is also significant to ensure women a greater participation in decision-making with respect to the mass media, increasing their opportunities to utilize the media to voice their opinions and facilitating women’s professional promotion in media institutions. These objectives were already embraced in the National Program in Aid of Women’s Rights that was implemented in Poland from 2003 through 2005. In 2010, the Helsinki Foundation for Human Rights and the „Feminoteka” Foundation stressed the issue of women’s discrimination in the Polish mass media. Monitoring of programs demonstrated that the principle of gender equality was not observed. The so-called female press is a significant element of the media market. The issues discussed in this sector usually concentrate on stereotypical female roles in society. Recently, however, a clear diversification of topics handled by the press can be noted and the efforts some periodicals are making in order to break gender stereotypes. Such attempts have been made by two new periodicals addressed mainly at women: „Bluszcz” and „Zadra”. An analysis of the content of „Bluszcz” did not evidence the abandonment of the traditional image of women though. A perusal of „Zadra” led to completely different conclusions. This is a feminist periodical that mainly discusses the issues of the social and political activity of women. The paper also emphasizes the increasing participation of women in the internet and in the social media.